Lidocaine as a potential anti-seizure therapy for pediatric FIRES: a promising therapeutic approach - Yang, Ying; Wei, Ningning; Guan, Qiao; Xie, Han; Huang, Xiaofang; Ru, Xifang; Wu, Ye; Wang, Ying; Sang, Tian (Frontiers in Pediatrics, 2025)
Febrile infection-related epilepsy syndrome (FIRES) is a catastrophic, drug-resistant epileptic encephalopathy characterized by acute onset following febrile illness and progression to (super-)refractory status epilepticus. We report a case of FIRES in a previously healthy 5-year-and-11-month-old boy who developed super-refractory status epilepticus (SRSE) on day 6 of a nonspecific febrile illness. The seizures were characterized by upward eye deviation, generalized tonic posturing, perioral cyanosis, and persistent impairment of consciousness. Despite comprehensive treatments including multiple immunotherapies (intravenous immunoglobulin administration, methylprednisolone pulse therapy, tocilizumab, and anakinra), ketogenic diet, multiple anti-seizure medications, and management of complications (intracranial pressure control, anti-infective therapy, and respiratory support), seizures remained refractory. Due to refractory seizures, intravenous lidocaine (3 mg/kg/h) was initiated after failed trials of midazolam, propofol and chloral hydrate, and only partial response to ketamine. With a consecutive 35-day infusion (cumulative duration >45 days), this regimen produced substantial reductions in both seizure frequency and severity, with clinically significant improvement in seizure control. Electroencephalogram (EEG) monitoring showed a decrease in the frequency and intensity of epileptic discharges, and improved background activity. The patient's level of consciousness also showed signs of improvement. This case is notable as few reports exist on the use of lidocaine in FIRES patients. It highlights the potential of lidocaine as a valuable anti-seizure option in FIRES management, suggesting the need for further investigation into its safety, efficacy, optimal dosage, and treatment duration in a larger cohort of FIRES patients.